Perbedaan Kadar Kalsium Femur Tikus Setelah Paparan Akut Dan Subkronik Debu Batubara - Karina Solikha Nurmalita; Zairin Noor; Bambang Setiawan (Berkala Kedokteran, 2013)
Abstract: Coal dust is a byproduct of coal processing and pollutants in coal mining area and transportation as well. After inhalation of coal dust, the particles will settle in alveoli of the lungs and spread through the vascular system by inflammatory process. The particles contain various minerals that increased substitution or incorporation process of bone mineral in hydroxyapatite lattice, include calcium. The aimed of this research was to determine the difference of Ca2+ levels in femur wistar rats caused by acute and subchronic coal dust exposure. This research was an observational analytic research. Subjects were male wistar rat bone samples taken from Bank Jaringan PEROSI Banjarmasin. Research subjects divided into seven groups: control, acute exposure (14 days) and subchronic exposure (28 days) each with an exposure dose at 6.25 mg/m3, 12.5 mg/m3, and 25 mg/m3. There were four samples femur in each group. Data were analyzed using Kruskal-Wallis test. The result did not show any significant differences of calcium levels in femoral bone wistar rats after acute (p=0,739) and subchronic exposure (p= 0,123). The conclusion, there were no significant differences of calcium levels in femur rats after exposure to coal dust with various dosage. Keywords: Calcium levels, coal dust, wistar rats, acute, subchronic. ABSTRAK: Debu batubara merupakan produk samping pengolahan batubara sekaligus polutan di area pertambangan dan transportasi batubara. Partikel tersebut mengandung berbagai macam mineral yang dapat memicu proses substitusi atau inkorporasi mineral tulang dalam kristal hidroksiapatit, salah satunya mineral kalsium. Penelitian bertujuan untuk mengetahui perbedaan kadar Ca2+ femur tikus wistar jantan akibat paparan debu batubara yang diberikan pada wakru berbeda. Penelitian ini merupakan penelitian observasional analitik menggunakan sampel tulang tikus wistar jantan yang diambil dari Bank Jaringan PEROSI Banjarmasin. Subjek penelitian dibagi dalam tujuh kelompok yaitu, kontrol, BB1 = dosis batubara 6,25 mg/m3, BB2 = dosis batubara 12,5 mg/m3, dan BB3 = dosis batubara 25 mg/m3, yang masing-masing diberi paparan akut (14 hari) dan paparan subkronik (28 hari). Berdasarkan hasil uji Kruskal-Wallis, disimpulkan bahwa tidak terdapat perbedaan bermakna apabila didapatkan nilai p<0,05. Hasil penelitian menunjukkan perbedaan kadar kalsium tulang femur tikus wistar jantan yang tidak bermakna setelah paparan akut (p=0,739) dan subkronik (p= 0,123). Tidak terdapat perbedaan bermakna dari kadar kalsium femur tikus setelah paparan debu batubara. Kata-kata kunci: Kadar kalsium, debu batubara, tikus wistar, akut, subkronik.